Image and video resizing algorithm based on importance diffusion and adaptive scaling - WANG Hui-qian1; YANG Gao-bo1; ZHANG Zhao-yang3; XIA Zhong-chao1 (Tongxin xuebao)
An image and video resizing algorithm was proposed based on importance map diffusion and adaptive scaling.It compromised between the protections of image content and important regions.To avoid the image distortion by exces-sive deletion of un-important regions,the importance of current row and column was spread to their neighboring pixels.To protect importance regions,different weighting coefficients were allocated to every row and column in terms of their importance by adaptive scaling function.Moreover,it was also effective for video resizing by incorporating the constraint of temporal coherency.Experimental results show that compared with other techniques such as cropping and seam carv-ing,satisfactory results were achieved by the proposed approach.